O niemieckim filmie propagandowym z warszawskiego getta. Przyczynek do analizy - Kubicki, Maciej (Zagłada Żydów. Studia i Materiały, 2006)
This article describes the circumstances in which a German crew shot a film in the Warsaw Ghetto in May and June 1942. The author employs visual materials and eyewitness' accounts of Warsaw Ghetto Jews. They are an important counterpoint, revealing the background and the persuasive dimension of the Nazi message. The text is aimed at an understanding of the propagandistic intention, rooted in the specifically Nazi techniques of persuasion. To do this, the author refers to the sources of anti-Semitic imaginarium and the modes of depiction of the Jew as an enemy figure. The reconstruction of the image of the Jewish community in this film is reinforced by references to broader ideological and socio-cultural contexts.